$e^+e^-$ hadronic cross-sections with SND detector at VEPP 2000 - T. V. Dimova, M. N. Achasov, A. Yu. Barnyakov, K. I. Beloborodov, A. V. Berdyugin, A. G. Bogdanchikov, A. A. Botov, V. P. Druzhinin, L. V. Kardapoltsev, A. G. Kharlamov, A. A. Korol, D. P. Kovrizhin, A. S. Kupich, N. A. Melnikova, A. E. Obrazovsky, E. V. Pakhtusova, K.V. Pugachev, S. I. Serednyakov, D. A. Shtol, Z. K. Silagadze, I. K. Surin, Yu. V. Usov, V. N. Zhabin (SciPost Physics Proceedings)
Data with an integrated luminosity of about 370 pb$^{-1}$ have been collected with the SND detector at the VEPP-2000 $e^+e^-$ collider. Here we present recent results on $e^+e^-$ annihilation into hadrons below 2 GeV based on a part of these data. In particular, we discuss measurements of the $e^+e^-→ π^+π^-$, $e^+e^- → n\bar{n}$, $e^+e^- → p\bar{p}$, and $e^+e^-→ π^+π^-π^0π^0$ cross sections, and study of the processes $e^+e^-→ π^+π^-π^0$, $e^+e^-→ K^+K^-π^0$, $e^+e^- → ηπ^0 γ$, and $e^+e^- → η η γ$.